Exosomal microRNAs in giant panda (Ailuropoda melanoleuca) breast milk: potential maternal regulators for the development of newborn cubs - Jideng Ma (Nature Portfolio, 2017)
Abstract The physiological role of miRNAs is widely understood to include fine-tuning the post-transcriptional regulation of a wide array of biological processes. Extensive studies have indicated that exosomal miRNAs in the bodily fluids of various organisms can be transferred between living cells for the delivery of gene silencing signals. Here, we illustrated the expression characteristics of exosomal miRNAs in giant panda breast milk during distinct lactation periods and highlighted the enrichment of immune- and development-related endogenous miRNAs in colostral and mature giant panda milk. These miRNAs are stable, even under certain harsh conditions, via the protection of extracellular vesicles. These findings indicate that breast milk may facilitate the dietary intake of maternal miRNAs by infants for the regulation of postnatal development. We also detected exogenous plant miRNAs from the primary food source of the giant panda (bamboo) in the exosomes of giant panda breast milk that were associated with regulatory roles in basic metabolism and neuron development. This result suggested that dietary plant miRNAs are absorbed by host cells and subsequently secreted into bodily fluids as potential cross-kingdom regulators. In conclusion, exosomal miRNAs in giant panda breast milk may be crucial maternal regulators for the development of intrinsic ‘slink’ newborn cubs.